The Epistemology of Al-Ghazali’s Thought on Khabar Mutawatir and Khabar Ahad - Alma?arif (Jurusan Tafsir Hadis Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
Some scholars regarded al-Ghazali as not a well-known expert of the hadith. They even stated that the weakness of al-Ghazali lies in the science of hadith. This article aims to refute those opinions by providing al-Ghazali’s thoughts on hadith, mainly on khabar mutawatir and khabar ahad, as well as the epistemic paradigm that construct his idea on hadith. I argue that al-Ghazali’s thought on hadith has a wide approach i.e. the use of logical and philosophical approach. This shows that al-Ghazali tends to be more inclusive in understanding hadi>th. Besides, I also argue that the use of logical and philosophical approach has to do with the political milieu where the Sunnite dynasty of Seljuq was in respond against the Shi‘ite Fatimid power of Egypt. The very intellectual milieu of the Fatimid dynasty was flourished by logic and Greek philosophy. As a Sunni defender of the Seljuq, it is a must to fight the intellectual Shi‘ite Isma’ilite of the Fatimid by mastering logic and philosophy. Thus, al-Ghazali’s usage of both approaches in the science of hadi>th was to justify and defend the authority of the Sunni Ash‘ari of the Seljuq dynasty.